Pengaruh Koordinasi Mata Tangan Dan Kekuatan Otot Lengan Terhadap Kemampuan Smash Siswa Ekstrakurikuler Bola Voli Di Smp Negeri 25 Seluma - Rory Rizki Pratama; Feby Elra Perdima; Martiani Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of hand-eye coordination and arm muscle strength on smashing ability in students participating in volleyball extracurricular activities at SMP Negeri 25 Seluma. The background of this study is based on the importance of smashing technique in volleyball, which requires a combination of precise coordination and muscle strength. The research method used is associative quantitative research. The study population was 22 students, all of whom were sampled using total sampling technique. The research instruments consisted of hand-eye coordination test, push-up test to measure arm muscle strength, and smashing ability test. The results showed that there was a significant effect of hand-eye coordination and arm muscle strength on students' smashing ability. Based on multiple linear regression test, both independent variables contributed significantly to the improvement of smashing ability, both partially and simultaneously. The average score of smashing test results increased from 15.73 in the pretest to 22.68 in the posttest. The Paired Samples Test produced a significance value of 0.000 < 0.05 with t_count 4.642, which means there was a significant difference between the initial and final test results. It was concluded that hand-eye coordination and arm muscle strength have an important role in improving students' smashing abilities.